Equity Structure, Green Innovation and Corporate Finance Constraints - Luan, Guiping (International Journal of Global Economics and Management, 2025)
Based on the goal of “dual carbon”, we select the data of Chinese A-share listed companies from 2007 to 2019, and empirically test the effects of equity structure, green innovation and their interaction terms on corporate financing constraints, and find that: (1) the improvement of equity checks and balances and green innovation can alleviate the financing constraints faced by enterprises, especially in SOEs. financing constraints, which is particularly significant in SOEs. (2) An increase in equity concentration and management shareholding can effectively alleviate the financing constraints of enterprises, and this effect is more significant in non-SOEs. (3) Considering the interaction effect of management shareholding and green innovation, the increase of management shareholding can weaken the mitigation of financing constraints by green innovation, and this effect is more significant in non-SOEs. This paper provides new empirical evidence for corporate financing constraints from the perspectives of equity structure and green innovation, which is conducive to optimizing the equity structure and improving the vitality of corporate green innovation development.